Zinc-finger protein MdBBX7/MdCOL9, a target of MdMIEL1 E3 ligase, confers drought tolerance in apple. Issue 1 (1st September 2021) - Chen, Pengxiang; Zhi, Fang; Li, Xuewei; Shen, Wenyun; Yan, Mingjia; He, Jieqiang; Bao, Chana; Fan, Tianle; Zhou, Shuangxi; Ma, Fengwang; Guan, Qingmei
Abstract: Water deficit is one of the main challenges for apple ( Malus × domestica ) growth and productivity. Breeding drought-tolerant cultivars depends on a thorough understanding of the drought responses of apple trees. Here, we identified the zinc-finger protein B-BOX 7/CONSTANS-LIKE 9 (MdBBX7/MdCOL9), which plays a positive role in apple drought tolerance. The overexpression of MdBBX7 enhanced drought tolerance, whereas knocking down MdBBX7 expression reduced it. Chromatin immunoprecipitation-sequencing (ChIP-seq) analysis identified one cis -element of MdBBX7, CCTTG, as well as its known binding motif, the T/G box. ChIP-seq and RNA-seq identified 1, 197 direct targets of MdBBX7, including ETHYLENE RESPONSE FACTOR ( ERF1 ), EARLY RESPONSIVE TO DEHYDRATION 15 ( ERD15 ), and GOLDEN2-LIKE 1 ( GLK1 ) and these were further verified by ChIP-qPCR and electronic mobility shift assays. Yeast two-hybrid screen identified an interacting protein of MdBBX7, RING-type E3 ligase MYB30-INTERACTING E3 LIGASE 1 (MIEL1). Further examination revealed that MdMIEL1 could mediate the ubiquitination and degradation of MdBBX7 by the 26S proteasome pathway. Genetic interaction analysis suggested that MdMIEL1 acts as an upstream factor of MdBBX7. In addition, MdMIEL1 was a negative regulator of the apple drought stress response. Taken together, our results illustrate the molecular mechanisms by which the MdMIEL1–MdBBX7 module influences the response of apple to drought stress. Abstract : A ubiquitin E3 ligase, MdMIEL1, mediates drought tolerance through the ubiquitination and degradation of MdBBX7 regulating its downstream gene activation in response to drought stress.